Analisa Yuridis Wanprestasi Terhadap Pembangunan Rumah Tahan Gempa : (Studi Putusan Nomor 27/PDT/2021/PT MTR) - Nur Aini Indrasari; Zaenal Arifin Dilaga (Fakultas Hukum Universitas Mataram, 2023)
This study aims to determine the legal considerations of the judge in granting the lawsuit for breach of contract for the construction of earthquake-resistant houses between CV. Graha Permata against UD. Ina Enterprise, as well as knowing the legal relationship of the parties in the default case against the RTG Development. This type of research is normative research, with the approach method used is the statutory approach (Statue Approach), conceptual approach (Conceptual Approach), and analytical approach (Analytical Approach). Based on the results of the study, the panel of judges stated that the defendant was proven to be in default, and the defendant had to pay material compensation to the plaintiff as the injured party, and in this case there were 2 legal relationships, namely between PPK and CV Graha Permata and CV. Graha Permata with UD. Ina Enterprise.